2009
DOI: 10.1159/000252969
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Amplitude-Integrated Electroencephalogram Patterns in Stable Preterm Infants, with Normal Neurological Development at One Year

Abstract: Background: The amplitude-integrated EEG (aEEG) is feasible for monitoring cerebral activity in preterm infants. However, quantitative data on normal patterns in these infants are limited. Objective: To study maturational aEEG changes in a cohort of stable preterm infants by automated quantification. Methods: In a cohort of stable preterm infants with gestational age (GA) <32 weeks and normal neurological follow-up at 1 year, weekly 4 h EEG recordings were performed. aEEG traces were obtained from channel C Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 72 publications
1
21
1
Order By: Relevance
“…To date, discrimination between artifacts and true biological activity mainly has been done by visual editing. The disadvantages of this method are that it is a time-consuming process and a subjective method strongly influenced by the interpreter (16). Trimming the unedited data by removing 5, 10, 15, or 20% of the highest power values, respectively, may give a more representative sample of the true EEG activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, discrimination between artifacts and true biological activity mainly has been done by visual editing. The disadvantages of this method are that it is a time-consuming process and a subjective method strongly influenced by the interpreter (16). Trimming the unedited data by removing 5, 10, 15, or 20% of the highest power values, respectively, may give a more representative sample of the true EEG activity.…”
Section: Discussionmentioning
confidence: 99%
“…Another problem is the lack of an algorithm for reliable EEG analyses and thus the dependency of the time-consuming visual editing for identifying and removing artifacts in a LTM (11)(12)(13)(14)(15). In addition, visual editing is a subjective method that requires high interpreter competence and experts may come to different conclusions (16).…”
mentioning
confidence: 99%
“…[41][42][43][44][45][46] Olischar et al 43 determined reference values of aEEG tracings in such infants, and characterized their background patterns as continuous, discontinuous high voltage and discontinuous low voltage. By monitoring this population over the first two weeks of life, this study showed that the amount of continuous activity increased with higher GA, whereas the amount of discontinuous activity decreased with higher GA.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we managed to obtain the accurate amplitude of the aEEG margin, which largely enhanced the objectivity of data interpretation. Quantitative aEEG margins can be obtained along with graphical tracing in some new digital aEEG devices (e.g., the NicoletOne monitor [19]) or in some off-line software (e.g., Brainz Analyze Research [5]). We believe that the aEEG algorithm, including margin display and quantitative output, can be used successfully for both individual CFMs and full-scale EEG monitoring systems.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum and minimum amplitudes in each epoch were detected as the upper and the lower terminal points of the associated aEEG vertical line. The time resolution of the compact aEEG was 15 s [19].…”
Section: Segmentation and Terminal Point Extractionmentioning
confidence: 99%